UV-Spectrophotometric Determination of Imatinib Mesylate - Gowri Sankar, D.; Madhavi Latha, P.V.; Vamsi Krishna, M. (Asian Journal of Chemistry, 2010)
A simple and sensitive UV spectrophotometric method has been developed for the determination of imatinib mesylate in pure as well as in pharmaceutical formulations. The drug exhibits maximum absorption at 255 nm and the method obeys Beer's law at the concentration range of 0.25–1.25 μg/mL. This method was extended to pharmaceutical preparations and there is no interference from any common pharmaceutical addivitves.